Back Massage in Reducing Anxiety and Back Pain in Third Trimester Pregnant Women - Agustina Gultom; Arbani Batubara; Masnila Masnila; Nurlama Siregar (Sarana Ilmu Indonesia (Salnesia), 2026)
Anxiety is a common problem among pregnant women, especially during the third trimester. Maternal anxiety refers to the experience of excessive and distressing worry, fear, and anxiety related to childbirth, concerns about the well-being of the developing fetus, and the challenges of parenthood. Lower back pain can reduce a pregnant woman's quality of life. Back massage is an intervention that can be offered to pregnant women in the third trimester to relieve anxiety and back pain. The aim of this study was to analyze the effect of back massage on anxiety and back pain in pregnant women in the third trimester. This quantitative research used a quasi-experimental approach with a pretest-posttest design for one group of 30 subjects, using consecutive sampling as the sampling technique. The research was conducted from July to December 2025 in the Mulyorejo Community Health Center Working Area, Deli Serdang Regency. The data collected were primary data, derived from guided interviews using a questionnaire. This study used the Perinatal Anxiety Screening Scale to assess maternal anxiety and the Numeric Rating Scale to assess back pain. Data were analyzed using IBM SPSS Stats 22 software using the Wilcoxon test with a 95% confidence level (p-value < 0.05). The study results showed a decrease in anxiety from 16.60 to 10.87, and a decrease in pain from 2.10 to 0.47, with p = 0.0001 for both outcomes. It can be concluded that back massage reduces anxiety and pain in pregnant women in the third trimester.